Addressing race-based stress in therapy with Black clients : using multicultural and dialectical behavior therapy techniques - Johnson, Monica M.; Melton, Michelle L. (New York, NY : Routledge, 2021)
"Despite Black Americans being at high risk for negative mental health symptoms due to racism and other chronic stresses, disparities persist in the provision of mental health services to this population. This book addresses that gap in clinical practice by explicitly calling attention to the experience of race-based stress in the Black community. Johnson and Melton urge mental health practitioners to action in promoting societal understanding, affirmation, and appreciation of multiculturalism against the damaging effects of individual, institutional, and societal racism, prejudice, and all forms of oppression based on stereotyping and discrimination. Chapters include worksheets, vignettes, and case studies to provide a practical framework for implementing an effective, nonpathological approach to ameliorating the damaging effects of race-based trauma and stress. This book will give tools and strategies for mental health professionals to responsibly use scientific and professional knowledge to improve the condition of individuals, communities, and, by extension, society"--
OCLC-licensed vendor bibliographic record.
Keywords: African Americans -- Psychology; Stress (Psychology) -- Treatment; Behavior therapy; Cultural competence; PSYCHOLOGY / Mental Health